HUBUNGAN IKLIM KESEHATAN DAN KESELAMATAN KERJA, KEPUASAN KESELAMATAN, DAN PERILAKU AMAN PEGAWAI TERHADAP KECELAKAAN KERJA DI UNIT BERISIKO RUMAH SAKIT PKU MUHAMMADIYAH YOGYAKARTA - , ARI WIBOWO, S.FARM. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The existence of positive paradigm-optimistic spawned theories that occupational accidents could be studied, so that it can be prevented. This study aims to determine the correlation and influence of safety climate dimensions, safety satisfaction, and safe behavior of workers against occupational accidents. This research is analytical study with cross-sectional survey design, using a questionnaire that contains four variables, namely, safety climate, safety satisfaction, safe behavior, and occupational accidents. Respondents consisted of the nursing paramedic, the non-nursing paramedics, as well as non-medical and had worked more than one year at the same risk unit. Also conducted a survey to know type of hazard at risk units. Data were analyzed using descriptive statistics, T-test, one-way anova, pearson correlation, and linear regression. Results for the eight-risk unit shows most accidents caused by common hazards (34.8%), ergonomics (39.6%), and physics (37.8%) occurred in the nutrition unit, due to biological hazards (36.2% ) and chemicals (34.5%) occurred in the Central Surgical Installation, whereas most accidents due to psychosocial hazards (30.5%) occurred in the Intensive Care Unit. T-test and avona shows a significant differences in safely behaviors of respondents by gender (p=0.004) and job position (p=0.005). There are also significant differences in safety satisfaction on respondents who had been safety trained (p=0.012). Findings suggested that there was negative correlation between safety climate, safety satisfaction, and safe behavior against occupational accidents (r= -0.161 until -0.378). Multiple regression analysis showed a significant correlation and influence between nine safety climate dimensions with safety satisfaction (R=0.591